2009
DOI: 10.1002/jat.1492
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between intronic variants in AS3MT and arsenic methylation efficiency is focused on a large linkage disequilibrium cluster in chromosome 10

Abstract: Differences in arsenic metabolism are known to play a role in individual variability in arsenicinduced disease susceptibility. Genetic variants in genes relevant to arsenic metabolism are considered to be partially responsible for the variation in arsenic metabolism. Specifically, variants in arsenic (3+ oxidation state) methyltransferase (AS3MT), the key gene in the metabolism of arsenic, have been associated with increased arsenic methylation efficiency. Of particular interest is the fact that different stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 43 publications
(54 reference statements)
2
43
1
Order By: Relevance
“…The associated genes such as AS3MT and GSTO1/2 highlight oxidative stress as a possible mechanism in arsenic biotransformation and therefore in arsenic-related diseases. Given the high LD in the 10q24 region in populations throughout the world (Fujihara et al 2010; Gomez-Rubio et al 2010), and particularly among the American Indians in our study, further investigation in comparable populations and using low-frequency variants is needed to confirm our findings. Further knowledge of causal variation may highlight biological mechanisms that are related to arsenic metabolism, including methylation, and may contribute to the elucidation of possible mechanisms for arsenic toxicity and the development of chronic diseases including skin lesions, cancer, and cardiovascular disease.…”
Section: Resultsmentioning
confidence: 67%
“…The associated genes such as AS3MT and GSTO1/2 highlight oxidative stress as a possible mechanism in arsenic biotransformation and therefore in arsenic-related diseases. Given the high LD in the 10q24 region in populations throughout the world (Fujihara et al 2010; Gomez-Rubio et al 2010), and particularly among the American Indians in our study, further investigation in comparable populations and using low-frequency variants is needed to confirm our findings. Further knowledge of causal variation may highlight biological mechanisms that are related to arsenic metabolism, including methylation, and may contribute to the elucidation of possible mechanisms for arsenic toxicity and the development of chronic diseases including skin lesions, cancer, and cardiovascular disease.…”
Section: Resultsmentioning
confidence: 67%
“…They were similarly associated with a SNP (rs743572) located near the gene CYP17A1 , 27 kbs upstream of AS3MT (Engstrom et al, 2009). Taken together, these results indicate the presence of a large haplotype block (pairwise LD analysis r 2 = 0.82) (at least 63 kbs in size, on chromosome 10) that can have a profound effect on health outcomes by altering the methylation of As (Gomez-Rubio et al, 2010). Sampayo-Reyes et al .…”
Section: Biological Markers Of Arsenic Exposure Metabolism Toxicmentioning
confidence: 72%
“…For example, in a study of a Mexican population that was exposed to arsenic in the drinking water, there were variations in arsenic methylation efficiency among individuals (Gomez-Rubio et al 2009). In another study of Bangladeshi adults whose diets were deficient in folate, it was found that variability in nutritional status may be a risk factor for arsenic toxicity (Gamble et al 2005).…”
Section: Future Perspectivesmentioning
confidence: 99%